THE EFFECTIVENESS OFTAGLINE "ADA AQUA" USING EPIC MODEL IN RANGKAPAN JAYA BARU SUB-DISTRICTPANCORAN MAS DEPOK - Ade Purwanto; Khoirul Umam (MBA - Journal of Management and Business Aplication, 2019)
One  measure  of  the  success  of  advertising  is  its  ability  to  create  perspective  space  in  the minds of audiences and consumers. Advertising as a message delivery tool that does not only function  to  provide  information,  persuasive  and  reminds  audiences,  but  must  also  have  an impact  on  consumers  in  the  form  of  purchasing  actions  and  attitudes  towards  products  as expected   by   producers.   This   study   aims   to   analyze   the   impact of   AQUA   product advertisements  with  the  tagline “Ada  AQUA”to  consumers  by  using  the  EPIC  model (Emphaty,  Persuation,  Impact,  Communication).  The  research  method  used  is  quantitative descriptive.  The  results  showed  that  AQUA  ads  with  the  tagline  "Ada  AQUA"  were  in  the effective  category  asevidenced  by  the  results  of  Emphaty  dimensions  of  4.15,  which  meant consumers  liked  and  were  interested  in  AQUA  ads.  The  persuation  dimensions  of  3.89 showed  AQUA  ads  were  able  to  strengthen  their  image  and  character  in  the  minds  of consumers, the Impact dimension of 3.93 shows consumers more easily recognize AQUA ads with  that  tagline  and  Communcations  dimensions  of  4.06  indicate  consumers  are  able  to remember AQUA ads well. Broadly speaking, the conclusions obtained are AQUA ads with the  tagline “Ada  AQUA”effective  in  delivering  the  message  to  the  target   audience (consumers)